2016
DOI: 10.1590/0103-8478cr20150750
|View full text |Cite
|
Sign up to set email alerts
|

Plant characters of broccoli determinants of head production

Abstract: The increasing consumption of single-head broccoli is due to several factors, among them there are food production in minimally processing form and the existence of hybrids that adapt to various climates, in addition to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…Additionally, broccoli mass decreased linearly with the amount of eggs deposited, when the first plants were ready for harvest. Our results therefore confirm that development delays and reduced plant growth during the growing season can lead to significant drops in head mass at harvest, at least when all plants are harvested in a row (Brandelero et al 2016). This result is interesting because plant mortality is currently regarded as the main damage caused by the cabbage root fly on broccoli (El Titi 1979;Estorgues 2005).…”
Section: Radicum Affects All Development and Growth Traits And Redsupporting
confidence: 77%
See 2 more Smart Citations
“…Additionally, broccoli mass decreased linearly with the amount of eggs deposited, when the first plants were ready for harvest. Our results therefore confirm that development delays and reduced plant growth during the growing season can lead to significant drops in head mass at harvest, at least when all plants are harvested in a row (Brandelero et al 2016). This result is interesting because plant mortality is currently regarded as the main damage caused by the cabbage root fly on broccoli (El Titi 1979;Estorgues 2005).…”
Section: Radicum Affects All Development and Growth Traits And Redsupporting
confidence: 77%
“…Plant mortality was also recorded. Plant growth was evaluated via two measurements: the product of the largest leaf length and width (thereafter called "relative leaf area"), known to be highly correlated with leaf area in Brassica crops (Olfati et al 2010;Cargnelutti Filho et al 2015;Tartaglia et al 2016) and the height above ground of the apical meristem (thereafter simply called "plant height" in the text), often used to give complementary information on plant growth (Kloen and Altieri 1990;Brandelero et al 2016).…”
Section: Plant Development and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…For the author [28], the analysis and interpretation of canonical weights involve examining the signal and its magnitude, so that the variables with relatively larger canon weights contribute more to the statistical variables and vice versa. Brandelero et al [29] studying broccoli plant characters that determined head production, found a weight of 0.64 in the variable that most contributes to the correlation. In this study, the highest weight was 0.87 for Mn s in crop 1, followed by Mn t in crop 1 (0.58), Mn t in crop 2 in the first and second functions (0.51).…”
Section: Resultsmentioning
confidence: 99%
“…Сведения о корреляционных связях между признаками у капусты брокколи приведены в работах Харламова, Лихацкого и Чередниченко, Костенко, Renaud и др., Brandelero и др. [8,9,13,14,15]. При этом сведения об изменениях корреляционных связей при разных сроках посадки малочисленны.…”
Section: The Study Of the Correlation Relationship Between The Signsunclassified